Detection of adulteration in anhydrous milk fat (ghee) using season variation in Butyro-refratometer reading studied by employing dry fractionation technique - kumar, Anil; Upadhyay, Neelam; Gandhi, Kamal; Naik, Satya Narayan; Sharma, Vivek (Indian Journal of Dairy Science, 2017)
Two common types of adulterants i.e. soybean oil (SO) and buffalo depot fat (BDF) were studied to carried out their detection in milk fat using Butyro-refractometer (BR) reading before and after dry fractionation. The study revealed that both the adulterants (SO and BDF) showed the higher average B.R. readings of 63.50 and 45.81 andÂ as compared to pure cow and buffalo milk fats of 41.76 and 40.75 respectively, before fractionation. The cow milk fat added with SO individually could be detected at 10 and 15 percent levels, while BDF remained undetectable. Whereas, in case of buffalo milk fat both the adulterants could not be detected individually at any of the levels studied (5, 10 and 15 percent), except 15 percent level of SO in buffalo milk fat. However, the adulteration of mixture of adulterants in both cow and buffalo milk fat samples could be detected at all the levels (5, 10 and 15 percent of each adulterants), except 5+5 (10) percent level in buffalo milk fat. It was observed from the study that fractionation technique has offered advantage in lowering the detection limit in case of mixture adulterated samples, as low as 5+5 (10) percent level could be detected using both S15 and L10 fractions in cow milk fat and using L10 fractions in buffalo milk fat.